Pengaruh Motivasi Kompetensi dan Lingkungan Kerja pada Kinerja Aparatur Penyuluh Keluarga Berencana - Dyah Retna Puspita (JIANA ( Jurnal Ilmu Administrasi Negara ), 2011)
This study analysed factors affecting the family planning extension apparatur’s perfor-mance and their impact to the volunteer’s performance. A number of 165 family planning extensionapparatur from the district of Bogor and Cianjur and Depok Residence of West Java Province wereparticipated in this study. LISREL program with ‘SEM’ (Structural Equation Model) was used inanalyzing data. The results showed that the family planning extension apparatur’s performancewere influenced significantly by competence and environment factors and nonsignificantly bytheir work motivation. The total impact of them was 64 percent. Their performance impacteddirectly to the volunteer’s performance with coefficient 0,70. The suggestion was that their perfor-mance must be improved by providing special training in leadership and professionalism and alsoby increasing their social environment and local government’s support in family planning.